Respiratory support strategies in the prevention of bronchopulmonary dysplasia: A single center quality improvement initiative - White, Heather; Merritt, Kamaris; Martin, Kirsti; Lauer, Emily; Rhein, Lawrence (Frontiers in Pediatrics, 2022)
Background and Objectives: Bronchopulmonary dysplasia (BPD) continues to be a significant morbidity affecting very preterm infants, despite multiple advancements in therapies to treat respiratory distress syndrome and prevent BPD. Local quality improvement (QI) efforts have shown promise in reducing unit or system-wide rates of BPD. In preterm infants born between 23- and 32- weeks’ gestation, our aim was to decrease the rate of BPD at 36 weeks corrected gestational age from 43% to 28% by January 2019. Methods: Directed by a multidisciplinary respiratory QI team, we gradually implemented the following interventions to reach our aim: (1) early initiation of non-invasive ventilation in the delivery room, (2) initiation of caffeine prior to 24 hours of life, (3) administration of early selective surfactant per a well-defined guideline, (4) continuation of non-invasive ventilation until 32 and 0/7 weeks corrected gestational age (CGA), and (5) a revision of the early selective surfactant guideline. Outcome measures included rates of BPD, and process measures included compliance with the above interventions. Results: A total of 509 infants with an average gestational age of 29 1/7 weeks and birth weight of 1254 (SD ± 401) grams were included. The rate of BPD in our unit decreased from a baseline of 43% to 19% from the start of the project in October 2016 until the first quarter of 2022 (p <0.00001). The greatest reductions in BPD rates were seen after the initiation of the guideline to extend non-invasive ventilation until 32 0/7 weeks CGA. The rate of severe BPD decreased from 22% to 9%. Conclusions : In preterm infants born between 23- and 32-weeks’ gestation, our local QI interventions to reduce rates of BPD were associated with a reduction in rates by 56%. Increased use of antenatal steroids and higher birth weights post- vs pre-intervention may have contributed to this successes.